(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
Modern medicine increasingly intertwines technical expertise with ethical, social, and humanistic values. Philosophical disciplines such as ethics, epistemology, and existentialism significantly influence medical practice by addressing complex moral and conceptual issues. Despite technological advancements, the integration of philosophical reasoning into daily medical decision-making remains insufficiently emphasized. This study explores the role of modern philosophy in enriching ethical standards, enhancing critical thinking, and promoting holistic healthcare within contemporary medical practice. Modern philosophy reinforces the ethical foundations of medicine through principles like autonomy and justice, deepens the humanistic and existential understanding of patient care, and strengthens critical reflection and intellectual rigor among healthcare professionals. The article highlights how philosophical inquiry bridges science and the humanities, ensuring that medical practice remains both technically sound and profoundly humane. Embedding philosophical reflection into healthcare can foster more ethical, effective, and compassionate medical systems, shaping a future where patient dignity, critical thinking, and moral responsibility are paramount.